Chemical composition and wound healing activity of inflorescences, leaves, wood, and bark of Marsdenia Erecta R. Br. (Apocynacear) - Tumen, Ibrahim; Akkol, Esra Kupeli; Pranovich, Andrey V.; Reunanen, Arkku; Yaman, Barbaros; Yaman, Barbaros (Parlar Scientific Publications, 2018)
Marsdenia erecta R. Br. is known to have positive effects and is therefore used to treat gastrointestinal disorders, rheumatism, and skin disorders in Turkey. The aim of this study was to investigate the wound healing activity and chemical constituents of wood, inflorescences, leaves, and bark of M. erecta. In this study, hydrodistillation and SPME (Solid Phase Microextraction) methods were compared for analysis of essential oils (EO), and chemical compounds of the essential oils were determined. The hydrodistillation method revealed components including ?-pinene, nonanal, safranal in inflorescences; ?-pinene, theaspirane, 3-hexenyl benzoate in leaves; theaspirane, ethyl palmitate, ethyl linoleate in wood; and eicosane in bark. As a result of SPME analysis, the main compounds detected were ?-pinene and terpinolene in inflorescences; ?-pinene, sabinene, 1-oc-ten-3-ol, ?-myrcene, limonene, ?-phellandrene, and ci -sabinene hydrate 4-terpineol in leaves; cyclosativene, ?-copaene, and ?-caryophyllene in wood; and 3-octanone, ?-copaene, dimethyldecalol, 4-ethyl-veratrol, and 4-vinylveratrol in bark. In i ro studies showed that the essential oil obtained from wood using the hydrodistillation method inhibits the hyaluronidase and collagenase enzymes and thus promotes the wound healing process. © 2021 Elsevier B.V., All rights reserved.
Keywords: Apocynaceae; Essential Oils; Hydrodistillation; R Deni Erec; Spme; Wound Healing